Pengaruh Budaya Organisasi Terhadap Etika Profesi Akuntansi - Santi Adella Damayanti (Jurnal Akuntansi Publik Nusantara, 2024)
The purpose of this study is to analyze the influence of organizational culture and accounting professional ethics on employee performance and to analyze the influence of organizational culture and accounting professional ethics on employee performance. Organizational culture plays an important role in a company because it motivates employees to work and along with employee work ethic, improves employee performance. Together with accounting ethics, it ensures protection and fairness of reporting, prevents fraud, and increases public trust in the accounting profession. By implementing the principles of accounting ethics and organizational culture, we aim to create a business environment based on transparency and integrity.